Usage of English lexical and grammatical features by Malaysian Chinese / Loh Lee Ching - Loh , Lee Ching (2017)
From the early nineteenth century, the British colonists brought English to Malaysia (Asmah, 2012). When English arrived on Malaysian shores, it came into contact with many languages of the pluralistic society of Malaysia. It went through various changes, adopting and adapting features of these languages in order to serve the different social and communicative needs of the locals. Malaysian English, a nativised variety developed, as a result of this process. The influence of Chinese on Malaysian English, however is “underemphasised” (Tan, 2009, p. 452). Hence, the purpose of this research is to understand the usage of the lexical and grammatical features found in the English used by Malaysian Chinese. In doing so, this study attempts to fill the knowledge gap, i.e. to see the impact of “Chineseness” in Malaysian English. This study offers authentic data giving a better understanding of the non-native variety of English as used by the local Chinese. Data were collected from the messaging apps of 56 participants. Using a qualitative approach, the data were then analysed based on an adapted version of the categorisation of nativization features in the study of Platt, Weber and Ho (1984), Gupta (1992), Lowenberg (1984) and Tay (1993). The findings suggest that through language contact, the lexical and grammatical features used by the Malaysian Chinese bear the features of the participants’ native language which is Chinese. Creative innovation, and code switching and code mixing are also found to be common features. This finding also proposes that the aspectual markers already or liao, got and finish in the Malaysian Chinese English are reflexes of Chinese aspectual markers 了 le, 有yǒu and 完 wán respectively. These Chinese features have been integrated into English through substrate influences as well as processes like simplification, rule generalization, borrowing, lexical shifts and translation.